Determinan Sikap Ibu Dalam Pemberian Imunisasi Booster DPT - Manungkalit, Maria; Astarini, Made Indra Ayu; Febiola, Yolla (JURNAL NERS LENTERA, 2021)
After the child has received basic immunization, parents need to carry out further booster immunization so that family health can be improved. Booster is one way to increase the immune system from several diseases, especially in adolescents whose immune systems have decreased. One of the recommended boosters is DPT. The purpose of this study is to determine the attitude of mothers in giving DPT booster immunization to adolescents. The research design used correlational with cross sectional approach. The population in this study were all mothers who have teenage children aged 10-18 years in RW 10, Manukan Kulon Village, Surabaya, while the samples taken from RT 5 and RT 7 were 41 people with a sampling technique using one cluster random sampling 25%. The instrument uses a questionnaire that has been tested for validity by the researcher. The results showed that the cognitive, behavioral, and emotional aspects significantly affected the mother's attitude (p